Fetomaternal outcome in operative vaginal delivery - B., Jeyamani; Dhasleema A., Nashreen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Operative vaginal deliveries (OVD) were performed with the help of vacuum or forceps in the second stage of labor when mother and foetus condition is threatening. A successful assisted vaginal delivery avoids caesarean section and its associated morbidity and implications for future pregnancy. The aim of the study was to assess the maternal and neonatal outcome of vacuum and forceps assisted vaginal deliveries. Methods: It was a retrospective comparative cross sectional study done in VMKVMCH, Salem in obstetrics and gynecology department, from the period of April to June 2021. All the mothers delivered by operative vaginal delivery were included. Mothers with multiple pregnancies, preterm and breech presentation were excluded. Data collected using patients information sheet and analysis was done using SPSS 23. P value <0.05 was considered significant. Results: The most common age group was 21-25 years of age in both groups and most commonly used in primigravida. The most common indication for forceps assisted delivery in our study was the prolonged second stage labour and in vacuum delivery was poor maternal effort. In our study, common complication noted was extended episiotomy followed by perineal tear in forceps group and vice versa in vacuum group. Cephalhematoma was found to be more common in vacuum and scalp and instrumental injuries were more common in forceps assisted vaginal deliveries. Conclusions: Operative vaginal deliveries helps in improving both maternal and foetal outcomes and reduces the caesarean delivery rate and vacuum significantly reduces maternal trauma than forceps. No difference noted in neonatal outcome.